THE DELIMITATION OF LANDSCAPE UNITS FOR THE PLANNING OF PROTECTION – THE EXAMPLE OF THE FORESTS BY UPPER LISWARTA LANDSCAPE PARK - Sobala, Michał (Quaestiones Geographicae, 2019)
The delimitation of landscape units can be helpful in the preparation of studies related to landscape protection and landscaping. The aim of this article is to propose the modification of the method of local landscape delimitation developed for the landscape audit for the needs of protected areas. The comparison of two methods of delimitation indicates that the same area can be assigned to different landscape types and subtypes. The proposed modification of the method of landscape unit delimitation allows a more detailed reflection of the landscape and its links to the administrative boundaries of administrative communities.